TBVAC2020: Advancing Tuberculosis Vaccines from Discovery to Clinical Development - Kaufmann, Stefan H. E.; Dockrell, Hazel M.; Drager, Nick; Ho, Mei Mei; McShane, Helen; Neyrolles, Olivier; Ottenhoff, Tom H. M.; Patel, Brij; Roordink, Danielle; Spertini, François; Stenger, Steffen; Thole, Jelle; et al. (Frontiers in Immunology, 2017)
TBVAC2020 is a research project supported by the Horizon 2020 program of the European Commission (EC). It aims at the discovery and development of novel tuberculosis (TB) vaccines from preclinical research in TB vaccine projects to early clinical assessment. The project builds on previous collaborations from 1998 onwards funded through the EC framework programs FP5, FP6 and FP7. It has succeeded in attracting new partners from outstanding laboratories from all over the world, now totaling 40 institutions. Next to the development of novel vaccines, TB biomarker development is also considered an important asset to facilitate rational vaccine selection and development. In addition, TBVAC2020 offers portfolio management that provides selection criteria for entry, gating and priority settings of novel vaccines at an early developmental stage. The TBVAC2020 consortium coordinated by TBVI facilitates collaboration and early data sharing between partners with the common aim of working towards the development of an effective TB vaccine. Close links with funders and other consortia with shared interests further contribute to this goal.